1977
DOI: 10.1084/jem.146.4.909
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive involvement of H-2D(b) or H-2K(d) product in the interaction between T-killer lymphocytes and syngeneic H-2(b) or H-2(d) viral lymphomas

Abstract: It was demonstrated previously that the cytolysis of murine viral lymphoma cells by anti-murine sarcoma virus (MSV) syngeneic T-killer lymphocytes was restricted by some products of the H-2 complex. The respective role of the products of different regions of the H-2 complex were studied with six H-2(b) and three H-2(d) lymphomas induced by five different type C viruses. They were tested in a classical chromium release test against anti-MSV T-killer cells obtained from different inbred strains of mice, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
34
1

Year Published

1978
1978
1983
1983

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 29 publications
7
34
1
Order By: Relevance
“…This conclusion is consistent with the considerable evidence that has accumulated demonstrating that, in the systems studied so far, the MLVinduced tumor cell surface antigens responsible for eliciting the anti-tumor immune response in vivo are not carried on the MLV gp70 molecule (Alaba et al, 1979, and for review see Kurth et al, 1979). Further we (Zarling et al, 1978) and others (Gomard et al, 1978) have reported that a wide variety of high-titer xenogeneic antisera, raised against gp70 antigens purified from different MLV isolates, were unable to block the MLV-immune T, target-cell interaction. Most attempts to specifically block this interaction using purified MLV gp70 antigens have also only been partially successful Ting and Rogers, 1977); problems of non-specific inhibition by virion proteins in this type of assay have been reported (Shellam et al, 1976), and, as such, the results of Enjuanes et al (1979) must be interpreted with care.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This conclusion is consistent with the considerable evidence that has accumulated demonstrating that, in the systems studied so far, the MLVinduced tumor cell surface antigens responsible for eliciting the anti-tumor immune response in vivo are not carried on the MLV gp70 molecule (Alaba et al, 1979, and for review see Kurth et al, 1979). Further we (Zarling et al, 1978) and others (Gomard et al, 1978) have reported that a wide variety of high-titer xenogeneic antisera, raised against gp70 antigens purified from different MLV isolates, were unable to block the MLV-immune T, target-cell interaction. Most attempts to specifically block this interaction using purified MLV gp70 antigens have also only been partially successful Ting and Rogers, 1977); problems of non-specific inhibition by virion proteins in this type of assay have been reported (Shellam et al, 1976), and, as such, the results of Enjuanes et al (1979) must be interpreted with care.…”
Section: Discussionsupporting
confidence: 86%
“…Recently, however, Enjuanes et al (1979) achieved blocking of cytotoxicity with a purified Moloney MLV gp70 preparation, suggesting a role for gp70 in the target antigen. In contrast, we (Zarling et al, 1978) and others (Gomard et al, 1978) have shown that, in total, nine out of 10 tested high-titer xenogeneic antisera reactive with a wide range of type-specific gp70 antigens do not block FMR-MLV immune T, lysis of target cells; mouse antisera against the particular H-2 K and/or D-region encoded antigens expressed on the target cells almost completely abrogate cytotoxicity.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…CTL specificity for target antigens was analyzed by two approaches: (a) addition of varying numbers of competitor target cells to the SXCr release cytotoxicity assay (5) and (b) addition of anti-H-2 sera at varying dilutions, in the absence of complement, to the 51Cr release cytotoxicity assay (1,11). The percentage of inhibition of CTL-mediated cytotoxicity by both approaches was calculated according to the formula: control -experiment/control × 100, where control was the specific cytotoxic activity detected in positive control wells; and experiment was the experimental cytotoxicity values obtained from wells containing competitor target cells or blocking antisera.…”
Section: Methodsmentioning
confidence: 99%
“…The latter argument is probably not valid, however, since in other experimental conditions, using low doses of infecting virus, anti-Friend CTL can be obtained as well in BALB/c mice (unpublished results). Furthermore, the association between H-2D molecules and virus particles is reportedly specific to the defective SFFV agent and not found with the competent helper virus (Chen and Lilly, 1979) while cross-reacting anti-FMR CTL can be produced with any type of FMR-inducing competent C-type viruses, all of them being restricted by H-2Db in the H-2b and H-2Kd in the H-2d haplotypes (Gomard et al, 1977). In the present experiments with Rauscher virions which induce typical FMRspecific H-2 restricted CTL (results not shown) an association was found mainly with H-2Dd which, in our experience, never functions as a CTL-restricting element, whereas the major restricting antigen H-2D was never detected.…”
Section: Discussionmentioning
confidence: 99%